Soil-Transmitted Helminth Infection and Macronutrient Intake among Stunted Toddlers in Panti Sub-district, Jember - Ghaiska Najma Amnur; Yunita Armiyanti; Irawan Fajar Kusuma; Leersia Yusi Ratnawati; Wiwien Sugih Utami; Bagus Hermansyah (Media Gizi Indonesia, 2025)
Soil-transmitted helminth (STH) infections are one of the most common infectious diseases in the developing world, with prevalence rates as high as 65%. STH infections generally affect the digestive system, which can reduce appetite and nutrient absorption. This study aimed to determine the association between STH infection and macronutrient intake in stunted toddlers aged 12-36 months in Panti Sub-district, Jember Regency. This study used observational analysis method with cross-sectional approach. The total number of subjects was 83 stunted toddlers. Data on STH infection were collected through fecal examination and 2x24 hour food recall questionnaire to assess their macronutrient intake. The results of the study showed that the prevalence of STH was 4.8% with species identified in the examinations such as Ascaris lumbricoides (2.4%) and hookworm (2.4%). The majority of macronutrient intake was considered sufficient for protein (77.1%), deficit for carbohydrate (94%) and fat (77.1%). Bivariate analysis using the contingency coefficient correlation test showed that there was no significant correlation between STH infection and macronutrient intake. Based on the results of this study, macronutrient intake may be influenced by other factors such as the role of parents in preparing nutritious food, economic status, and mild degree of infection. However, the underlying mechanism remains unclear and should be further investigated.